Development of Genetic Transformation Protocol for Selected Elite Clone of Populus Deltoides - Kalra, Preeti (My University, 2014)
Various factors influencing shoot regeneration and transformation of a selected elite clone of Populus deltoides were standardized. An efficient protocol of Agrobacterium tumefaciens mediated T-DNA delivery and subsequent shoot regeneration has been developed. Different factors influenced T-DNA delivery as evident from transient GUS assay. The transient GUS expression was significantly higher in explants that were pre-cultured before bacterial infection on medium supplemented with 100 μM acetosyringone. Method of injury to explant, co-cultivation period of 2 days, bacterial density of 0.6 OD600 and 16 h photoperiod during co-cultivation showed higher transient GUS expression. Following co-cultivation, shoot organogenesis was achieved from leaf segments on modified MS medium containing 58 mM sucrose. Between two strains of A. Tumefaciens namely, EHA105 and LBA4404 (harbouring pBI121 plasmid), strain LBA4404 was found to be more efficient. Between two clones of P.deltoides tested, maximum transient GUS activity was recorded in clone ‘L34’. Different concentration of antibiotic was investigated to check the sensitivity of leaf explants. Supplementation of antibiotics (cefotaxime) at 500 mg/l into the medium significantly promoted shoot organogenesis from leaf explants. Stable transformation of regenerated shoots was confirmed on the basis of GUS activity.
MT, DBTS
Keywords: Agrobacterium tumefaciens LBA4404, Genetic transformation, GUS assay, Populus deltoides